Antifungal activity of zinc oxide nanoparticles (ZnO NPs) on Fusarium equiseti phytopathogen isolated from tomato plant in Nepal - Bimala Subba; Ganga Bir Rai; Rashmi Bhandary; Puja Parajuli; Niru Thapa; Dharma Raj Kandel; Sushika Mulmi; Sabita Shrestha; Sailesh Malla (Heliyon)
Fungal diseases pose a major threat to global agriculture, leading to reduced crop yields, health issues and significant economic impact. Application of nanoparticles are being explored in agriculture because of its ecofriendly as well as enhanced antimicrobial properties. In this study, using an aqueous extract of air-dried tea leaves, zinc oxide nanoparticles (ZnO NPs) are synthesized and it was characterized using various techniques such as X-ray diffraction, UV–Vis, FTIR spectroscopy and microscopic analysis. The growth inhibition activity of the ZnO-NPs was investigated against a phytopathogenic fungus, which was isolated and identified as Fusarium equiseti from tomato plant leaves. Our result showed that application of ZnO NPs at 750 ppm–1200 ppm concentration range inhibited the growth of F. equiseti by 77.6 %–85.1 % at 7 days of seeding the fungi in PDA media. Microscopic observation of the fungal strain treated with ZnO NPs showed that the presence of the nanoparticles agglomerates the normal hyphae of F. equiseti and formed curve tips and breakage of mycelia. Hence, our study shows that application ZnO NPs is promising approach for fungal growth inhibition and can be deployed to inhibit other plant diseases causing microbes in agriculture.